Paradox and paraconsistency : - Woods, John (Cambridge University Press, 2003)
In a world plagued by conflict one might expect that the exact sciences of logic and mathematics would provide a safe harbor. In fact these disciplines are rife with internal divisions between different, often incompatible systems. This original book explores apparently intractable disagreements in logic and the foundations of mathematics and sets out conflict resolution strategies that evade these stalemates. This book makes an important contribution to such areas of philosophy as logic, philosophy of language and argumentation theory. It will also be of interest to mathematicians and computer scientists